Glaucoma Clinic Monitoring Over 6 Months Using Online Circular Contrast Perimetry in Comparison with Standard Automatic Perimetry: The Developing-World Setting - Hoang TT; Mai TQ; Pham DT; Nguyen XT; Nguyen DA; Vu DT; Hoang HT; Nkurunziza M; Bigirimana D; Skalicky SE (Clinical Ophthalmology)
Tung Thanh Hoang,1,2 Tung Quoc Mai,1 Dung Thi Pham,1 Xuan Thi Nguyen,1 Duc-Anh Nguyen,1 Diu Thi Vu,1 Hien Thi Hoang,1 Menus Nkurunziza,3 Deus Bigirimana,4– 6 Simon Edward Skalicky4,5 1Ophthalmology Department, Hanoi Medical University, Hanoi, Vietnam; 2Ophthalmology Unit, Hanoi Medical University Hospital, Hanoi, Vietnam; 3Centre for Mathematics and Physics, University of Burundi, Bujumbura, Burundi; 4University of Melbourne, Department of Surgery, Melbourne, Victoria, Australia; 5Glaucoma Investigation and Research Unit, The Royal Victorian Eye and Ear Hospital, Melbourne, Victoria, Australia; 6Centre for Eye Research Australia, The Royal Victorian Eye and Ear Hospital, Melbourne, Victoria, AustraliaCorrespondence: Tung Thanh Hoang, Hanoi Medical University, No. 1 Ton That Tung Str, Dong Da Distr, Hanoi, 11518, Vietnam, Email tung.hoang@sydney.edu.auPurpose: Online circular contrast perimetry provides visual field testing on any computer or tablet without additional hardware. This study compared outcomes of online circular contrast perimetry (OCCP) and standard automated perimetry (SAP) in a developing world setting.Methods: The longitudinal and observation study was conducted on patients sampled during 2023 at Hanoi Medical University Hospital. Participants were either healthy volunteers as controls or stable glaucoma patients with either primary angle closure or primary open-angle glaucoma. They underwent a comprehensive ocular examination, retinal nerve fiber layer optical coherence tomography scan, and visual field tests performed at baseline and after 3 months and 6 months, using OCCP and SAP in clinic.Results: The current study was carried out in 168 eyes of 87 patients at baseline, 133 eyes of 69 patients at 3 months, and 121 eyes of 63 patients at 6 months. At baseline, OCCP mean deviation (MD) (R2 = 0.804, p < 0.001) and visual index (VI) (R2 = 0.892, p < 0.001) were strongly correlated with SAP MD and visual field index (VFI) respectively. There was strong agreement and correlation between MD and VI/VFI for SAP and OCCP on repeated testing after 6 months. At 6 months AUC of SAP VFI (0.79) was superior to AUC of OCCP VI (0.67, p = 0.036); otherwise there was no difference in AUC of MD or VI/VFI at baseline, 3 and 6 months, when comparing OCCP and SAP.Conclusion: OCCP parameters are significantly correlated with those of SAP. OCCP has the potential to provide a complementary role to SAP in glaucoma screening and monitoring.Keywords: glaucoma, online circular contrast perimetry